God of my enemy : the Middle East and the nature of God. - Reitsma, Bernhard, 1965- (Regnum Books International, 2014)
The establishment of the State of Israel in 1948 was the starting point for the church of the West of rediscovering its roots. In the Middle East the effect has been exactly the opposite: Christians have become estranged from their Old Testament roots, because they have been expelled from their land exactly because of an appeal to the Old Testament. The concept of Israel changed from a nation in the Bible, with which they could associate, to an economic, political, and military power that was against them. This book is an in-depth, clear, and intelligible perspective on the crucial issue of the land of Palestine. This is not a distant theological and biblical treatment, but has its relevancy and implications on both local and global scenes in the 21st century.